Currency union and real exchange rate behavior - LOTHIAN JAMES, R.; MCCARTHY, CORNELIA (Revista Momento Económico, 2009)
IN THIS PAPER WE STUDY THE BEHAVIOR OF THE REAL EXCHANGE RATE OF THREE AMERICAN CURRENCIES RELATIVE TO THE U.S. DOLLAR: THE CANADIAN DOLLAR, THE MEXICAN PESO ANS THE PANAMANIAN BALBOA. OUR PRINCIPAL OBJECTIVE IN DOING SO IS TO INVESTIGATE THE EFFECTS OF ALTERNATIVE EXCHANGE-RATE REGIMES, INCLUDING CURRENCY UNION, ON REAL EXCHANGE RATE BEHAVIOR. IN ECAH OF THESE THREE CASES WE FIND AT LEAST SOME EVIDENCE SUPPORTING THE PURCHASING POWER PARITY HYPOTHESIS IN THE DATA THAT WE EXAMINE. OUR SECOND SET OF CONCLUSIONS CONCERNS THE CRITICISMS RECENTLY DIRECTED AT THE EMPIRICAL EXCHANGE-RATE LITERATURE. AN IMPORTANT CRITERION UNDERLYING OUR CHOICE OF COUNTRIES WAS DIVERSITY OF EXPERIENCE WITH REGARD TO THE EXCHANGE-RATE REGIME. THE OBJECTIVE WAS TO DESIGN AN EXPERIMENT IN WHICH MEANINGFUL COMPARISONS OF BEHAVIOR ACROSS REGIMES WOULD BE POSSIBLE.